Global asymptotic convergence results for multitype models - Rass, Linda; Radcliffe, John (Zielona Góra: Uniwersytet Zielonogórski)
This paper proves global asymptotic convergence in a multitype epidemic model which encompasses both the S -> I and S -> I -> S epidemics. Systems are considered where the infection matrix may be reducible, and for which the system may be closed or can be open with a stable population size. New global asymptotic convergence results are obtained.
Keywords: global asymptotic convergence; multitype S -> I -> S epidemics; stable population size; reducible systems